"But the Child Is Flighty, Playful, Curious": Working-Class Boyhood and the Policing of Play in Belle Époque Paris. Issue 2 (1st June 2019) - Sachs, Miranda
Abstract : By the end of the nineteenth century, working-class children increasingly fell under adult supervision. Working-class boys, however, retained much autonomy over their leisure time. By examining memoirs and police archives, this article shows that boys' play often flirted with the criminal or the dangerous. When boys entered the workplace, this reputation for lawless play followed them. Drawing on accident reports, this article demonstrates that employers and republican labor inspectors blamed boys for dangerous workplace accidents by highlighting boys' playful nature. The article concludes by showing how reformers constructed spaces for boys' leisure in an attempt to tame and direct their play. I argue that this reckless play became one of the defining characteristics of working-class boyhood both within peer society and to external observers. Regulating boys' play thus became a way to ensure that they matured seamlessly into worker-citizens.